Thioxanthone-Fluorenes as Visible Light Photoinitiators for Free Radical Polymerization - Yilmaz, Gorkem; Aydogan, Binnur; Temel, Gokhan; Arsu, Nergis; Moszner, Norbert; Yagci, Yusuf (AMER CHEMICAL SOC, 2010)
Two thioxanthone derivatives with fluorene additional chromophoric groups, namely thioxanthone-fluorenecarboxylie acid (TX-FLCOOH) and thioxanthone fluorene sodium carboxylate (TX-FLCOONa), as visible light absorbing oil- and water-soluble photoinitiators, respectively, were synthesized and characterized. Their ability to initiate photopolymerization of methyl methacrylate (M MA), 2-(2-phosphonoethoxymethyl)acrylic acid ethyl ester (EAEPA), and a multifunctional monomer, trimethylolpropane triacrylate (TMPTA), were examined. The initiation efficiency of TX-FLCOOH was compared with the parent thioxantone (TX) both in the presence and in the absence of a co-initiator, and TX-FLCOOH was found to be more effective in :ill cases. Photopolymerization and laser flash photolysis studies revealed that depending on the concentration initiation by TX-FLCOOH occurs by intra and intermolecular H-abstraction of the triplet (3)(TX-FLCOOH)*. No polymerization was observed when TX-FLCOONa was used as photoinitiator in the absence of a co-initiator. However, TX-FLCOONa acts as an efficient initiator in the visible range in the presence of H donors in water.
Keywords: ACYLGERMANE-BASED PHOTOINITIATOR; WATER-SOLUBLE PHOTOINITIATORS; SIDE-CHAIN THIOXANTHONE; PHOTOCLEAVABLE STRUCTURES; CATIONIC-POLYMERIZATION; COINITIATOR AMINE; PHOTOPOLYMERIZATION; DERIVATIVES; MACROPHOTOINITIATOR; PHOTOCHEMISTRY; Polymer Science